Seryum (III)'ün eser florimetrik tayininde yeni raktifler - Rakıcıoğlu, Yener (Fen Bilimleri Enstitüsü, 1998)
Ce(lll) sulu çözeltide, sodyum pirofosfat, sodyum trifosfat, sodyum trimetafosfat, sodyum tetrametafosfat ve sodyum hegzametafosfat ile çok yüksek floresans göstermektedir. Bu reaktiflerle Ce(lll)'ün florimetrik olarak tayininin mümkün olup olmadığı araştırılmış ve bu amaçla aşağıdaki çalışmalar yapılmıştır. Her bir reaktif için önce uyarılma ve emisyon dalga boyları bulunmuştur. Sabit tutulan Ce(lll) konsantrasyonlarına karşı herbir reaktifin maksimum floresans gösteren konsantrasyonları belirlenmiştir. Reaktiflerin maksimum floresans gösterdikleri ortamlarda, floresans şiddetinin zamanla değişimi ara ara yapılan ölçümlerle ve devamlı ışınlama altında incelenmiştir. pH'ın floresans şiddeti üzerindeki etkisi her bir reaktifle tayin için incelenmiş ve uygun pH alanları bulunmuştur. Sıcaklığın floresans şiddeti üzerine etkisinin incelenmesiyle ölçümlerin oda sıcaklığında yapılabileceği görülmüştür. Diğer lantanitlerin ve bazı anyonların girişimlerinin incelenmesiyle düşük konsantrasyonlardaki lantanitlerin önemli bir etkilerinin olmadığı, CI", NO3", S042" anyonlarının girişim yapmadığı, PO43" anyonunun ise önemli ölçüde söndürme etkisinin olduğu belirlenmiştir. Farklı Ce(lll) konsantrasyonları için reaktiflerin maksimum floresans veren konsantrasyonlarında standart sapmalar hesaplanmış, uygun değerler bulunmuştur. Yöntemler sentetik olarak hazırlanan bazı karışımlardaki Ce(lll) tayinlerinde başarı ile uygulanmıştır. Kalibrasyon eğrilerinden her bir reaktif için lineerlik alanları ve tayin sınırları saptanmıştır. Bulunan değerler, literatürde verilen diğer yöntemlerle karşılaştırıldığında bu çalışmada sunulan yöntemlerin genel olarak önceki yöntemlere göre floresans şiddetlerinin yüksek, tayin sınırlarının düşük, lineerlik alanlarının geniş olması üstünlüğünün olduğu görülmektedir. Ayrıca ölçümler oda sıcaklığında, pH ayarlamaya dolayısıyla tampon çözelti kullanmaya gerek olmadan yapılabilmektedir.

Lanthanides are defined as the group of elements of atomic number 57-71 from lanthanum through lutetium. Scandium atomic number 21 and yttrium atomic number 39, have properties which are similar to the rare earths, and they occur in nature together with the lanthanides. Lanthanides with scandium and yttrium are named rare earths. The unique properties of the lanthanide elements are directly attributable to their electron configuration. The filling of atomic orbitals as predicted by the Aufbau principle is the basis for the construction of the periodic table. Looking at the sixth row of elements, one can see that the filling proceeds as predicted through atomic number 57 (lanthanum), which has the configuration [Xe]6s2d1. Following La, the energy levels of the 4f orbitals fall below the 5d's, and the next 14 elements (atomic numbers 58-71, that is cerium through lutetium) involve the filling of the 4f orbitals. Since these orbitals place the electrons nearer the center of the atom than the already present 5s25p66s25d1 electrons, the addition of the 4f electrons has little effect on the chemistry of these elements. On the other hand, magnetic and spectroscopic properties are highly affected. The chemistry of the lanthanides is quite similar to that of the Group III elements. One would expect this since the outermost, or valence electrons are the 6s25d1 for all 14 elements. This means that they all have stable +3 oxidation states, and that they are all very similar to each other, presenting a considerable challenge to those wishing to chemically separate them. Although the 4f electrons are too strongly bound and shielded to be involved in the chemistry of the lanthanide elements, their presence is directly responsible for the spectral and magnetic properties. Almost all of the lanthanides have unpaired electrons in the 4f levels (in Lu, 4f14, the 4f s are completely filled) even in the +3 oxidation state, making them all paramagnetic. There is considerable spin-orbit coupling and ISC is enhanced in organic ligands associated with these metal ions. XIII Lanthanide ions themselves have very low absorption and emission probabilities as the transitions of interest are generally forbidden; thus in the absence of a strongly absorbing ligand, luminescence is comparatively weak. The emission consists of several discrete narrow (1-20 nm) bands, each of which may demonstrate some additional splitting due to ligand field effects. When a suitable, strongly-absorbing ligand or chelator with appropriately situated energy levels is bound to lanthanide ion, absorption of light into the first excited singlet state of the ligand can be followed by intersystem crossing to the ligand triplet state and energy transfer to the lanthanide ion. Luminescence characteristic of the lanthanide ion will follow. The lanthanides have became more and more important in science and industry. Therefore they have found an increasing interest. And analysis techniques having a high power of detection for the rare earths are required. Since the chemical properties of the lanthanides are very similar, it is difficult and important to find specific reactions for individual ions, especially in their mixtures. Analytically, cerium is usually differentiated from its lanthanide family members on the basis of the strong oxidizing power of cerium(IV) in acidic solution. Addition of small amounts of cerium to steel significantly modified its properties. Similarly the addition of cerium to the different alloys give them useful properties. Therefore, the accurate determination of cerium at trace level is very important industrially. Several absorption photometric methods are based on the ability of cerium(IV) to oxidize organic reagents to coloured products. Since fluorimetric methods are inherently more sensitive and selective than absorption methods, it was considered worthwhile to develop the fluorimetric procedures for the determination of trace amounts of this increasingly important element. The determination of trace amounts of cerium has been accomplished by several workers. But these methods present difficulties especially when the analysis are made in the region below to ngml"1 cerium. Most of these fluorimetric methods are based on the fluorescence of cerium(lll) in dilute sulphate and chloride solutions at different pH but several interfering species (e.g. CI", N03", and P043") exist in the acidic media [3-19]. A fluorimetric determination of cerium by means of sulphonaptholazoresorcinol has been reported by C.T. Hjeu et al [24]. A fluorimetric method for the determination of cerium (IV) has been based on the oxidation of oxine-5-sulphonic acid in sulphuric acid medium [27] A.Navas et al have been reported that the reagent sodium 4,8-di-amino-1,5- dihydroxyanthraquinone-2,6-disulphonate is transformed in strongly acidic XIV medium into a pink highly fluorescent product by means of the oxygen dissolved in water[28]. This reaction is slow and takes two months to reach completion. Another fluorimetric determination of cerium has been accomplished by F.Salinas et al based on the oxidative reaction between cerium(IV) and 1-amino-4-hydroxyanthraquinone[29]. And a recent study for the fluorimetric determination of cerium(IV) based on the oxidative reaction between cerium(IV) and paracetamol, has been developed by NJie et al[1]. The fluorescence intensity of the system reaches maximum after heating at 100°C for 10 minutes and then remains stable for 2 hr. In this study, it has been investigated the possibilities of the fluorimetric trace determination of Ce(lll) in pyrophosphate, triphosphate, trimetaphosphate, tetrametaphosphate and hexametaphosphate media. Ce(lll) fluoresces strongly in pyrophosphate, triphosphate, trimeta phosphate, tetrametaphosphate and hexametaphosphate solutions when irradiated with ultraviolet radiation and it is the only lanthanide ion which is appreciably fluorescent under these conditions. Other lanthanides do not show any measurable fluorescence in these solutions. For these reagents, the maximum excitation\emission wavelengths are 30QA350 nm, 303.5V353 nm, 297\340 nm, 299\352 nm and 304\344 nm, respectively. Experimental results showed that Ce(lll) ions in the presence of these reagents are much more fluorescent than those in pure aqueous solutions and in presence of only sulfuric acid and hydrochloric acid. The effect of the concentrations of these reagents on the fluorescence intensities were studied and maximum fluorescence intensities are obtained by Ce(lll) dissolved in 0.033 gl'1 sodium pyrophosphate, 0.074 gl"1 sodium triphosphate, 41.4 gl"1 sodium trimetaphosphate, 0.96 gl"1 sodium tetrametaphosphate and 5.346 gl"1 sodium hexametaphosphate at room temperature. The effect of time on the fluorescence intensities were investigated for normal and continuous irradiation conditions and it is found that stabilities of fluorescence with time are excellent for the fluorimetric measurements. Effect of pH was studied by adjusting the pH with sulfuric acid or sodium hydroxide solutions and it has been seen that the fluorescence intensities are maximum and constant in the pH range (5.30)-(8.95) for pyrophosphate, (5.70)-(9.35) for triphosphate, (0.00)-(8.00) for trimetaphosphate, (3.70)- (9.00) for tetrametaphosphate and (3.25)-(9.20) for hexametaphosphate. After using a series of different buffer systems, it was found that borax- hydrochloric acid buffer can be used without causing any quenching. XV Nevertheless, in these studies no buffer was used because the pH of the solutions were always in the maximum range during the entire procedure. Effect of temperature was studied for different temperatures and it was found that it was not pronounced between 5-50°C for pyrophosphate, 10-50°C for triphosphate, 5-70°C for trimetaphosphate, 5-60°C for tetrametaphosphate and 5-70°C for hexametaphosphate. Room temperature is recommended for all measurements. The calibration graphs for the determination of Ce(lll) were constructed under optimum conditions. Good linearities were obtained over the ranges 0.05-30 ^gml"1 Ce(lll) for pyrophosphate, 0.005-45 jagml"1 Ce(lll) for triphosphate, 0.006-75 jagml"1 Ce(lll) for trimetaphosphate, 0.02-70 ngml"1 Ce(lll) for tetrametaphosphate and 0.03-60 ngml"1 Ce(lll) for hexametaphosphate. The limits of detection are 9.5x1 0'3 pgml'1 Ce(lll), 9.4x1 0"4 ngml"1 Ce(lll), 1.1x10"3 jagml"1 Ce(lll), 3.8x1 0"3 ı^gml"1 Ce(lll) and 6.0x1 0"3 (igmf1 Ce(lll), respectively. They were calculated by multiplying the standard deviations of 16 blank measurements by three and dividing by the slopes of the linear calibration curves. Interference effects of some other lanthanides and diverse inorganic anions on the fluorescence intensities were investigated. It has been seen that there is no significant interference for diverse anions and for the low concentrations of other lanthanides. The precisions were determined by measuring 16 solutions of the same sample 16 different times. The coefficients of variation were found approximately 1%. The procedures were applied to the determination of trace amounts of Ce(lll) in some synthetic mixtures. The results indicate that the proposed methods are suitable and can be successfully applied. In Table 1, some selected methods for the fluorimetric determination of cerium are listed. From the comparison of these methods, it can be seen that the methods proposed in this study are very suitable because of their high fluorescence intensities, sensitivities and wide linear ranges. As can be seen from the results presented in this study, the trace determination of cerium(lll) with sodium pyrophosphate, sodium triphosphate, sodium trimetaphosphate, sodium tetrametaphosphate and sodium hexametaphosphate are five simple, sensitive and selective new alternative methods for the direct fluorimetric determinations of cerium(lll). XVI Table 1. Summary of several of the best methods in the fluorimetric determination of cerium.
Tez (Doktora)-- İTÜ Fen Bil. Enst., 1998.
Thesis (Ph.D.) -- İstanbul Technical University, Institute of Science and Technology, 1998
Keywords: Kimya; Flüorometrik tayin; Seryum; Chemistry; Flüorometrik tayin; Seryum